Urban Environmental Management Practices and Green Roof Technologies in Malaysia: A Path to Sustainable Development - Zulkifly, Mohd Hashim; Madelyn Shiu Liu (Civil and Sustainable Urban Engineering, 2024)
Malaysia is the developing country, which develop in contraction, agriculture, and many more kinds of activities. The construction activities for Malaysia is less implemented the green materials technology and the Environmental Management. The Environmental Management Practices is not usually applied by the construction workers. The government also show no enforcement and awareness on the Environmental Management Practices in Malaysia. There are some importance of the Environmental Management Practices is described and also the plan to improve the implementation of Environmental Management Practices under construction of Malaysia. The green roof is one of the technologies of green materials. There three kinds of green roof system as intensive green roof system, semi-intensive green roof system, and extensive green roof system. These three different systems have its own advantages and this advantages. The green materials that can be used for the green roof construction are bamboo, stones, and recycled bricks. The green materials or green roof system help to reduce the environment impact, social impact, and economic impact of Malaysia. The better environment, social life and economic can lead to sustainable development in Malaysia.